2016
DOI: 10.1177/1091581816670597
|View full text |Cite
|
Sign up to set email alerts
|

A 28-Day Repeated Dose Toxicological Study of an Aqueous Extract of Morus Alba L.

Abstract: Morus alba L. (white mulberry) leaves are one of the oldest recognized traditional Chinese medicines. More recently, M alba leaves and their constituents, particularly iminosugars (or azasugars), have garnered attention for their ability to maintain normal blood glucose concentrations, an effect identified in both animal studies and human clinical trials. Reducose (Phynova Group Limited) is a commercial water-soluble extract of M alba leaves standardized to 5% 1-deoxynojirimycin (DNJ), an iminosugar with α-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…These findings suggest that daily administration of Q-Actin to rats at doses up to 1000 mg/kg bw/day (the highest dose tested) for 90-days was well tolerated. The findings of this study are supported by a previous 28-day rat toxicity study in which mulberry leaf extract containing iminosugar (5% DNJ) did not reveal any adverse effects and the NOAEL was found to be 4000 mg/kg bw/day [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings suggest that daily administration of Q-Actin to rats at doses up to 1000 mg/kg bw/day (the highest dose tested) for 90-days was well tolerated. The findings of this study are supported by a previous 28-day rat toxicity study in which mulberry leaf extract containing iminosugar (5% DNJ) did not reveal any adverse effects and the NOAEL was found to be 4000 mg/kg bw/day [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
“…The biological activities of iminosugar does not indicate potential for toxicity. A 28-day repeated dose toxicity study in rats using a commercially available mulberry leaf extract standardized to 5% DNJ, found no safety concerns [ 22 ]. This study concluded that the no observed adverse effect level was 4000 mg/kg bw/day (the highest dose tested), supporting the safety of DNJ and similar iminosugars.…”
Section: Discussionmentioning
confidence: 99%
“…Our safety results are consistent with the findings of previous studies, which showed that the singular ingredients used in Tribitor ® (MarMar Investment Sp. z o.o., Warsaw, Poland) do not have any serious side effects and that the gastrointestinal side effects are rare and diminish upon extended use of the products [ 33 , 34 ]. Taking into account the issues of cost and the potential side effects of other weight-loss drugs available, Tribitor ® (MarMar Investment Sp.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, intraperitoneal administration of 300 and 2,000 mg/kg bw of mulberry leaf ethanol extracts for 14 days induced a greater degree of toxicity toward biochemical, hematological, and histological parameters in mice [ 30 ]. In the current study, aqueous extracts of mulberry leaves administered orally at doses of 1,000, 2,000 and 4,000 mg/kg bw did not induce any significant alterations in bw/weight gain, food consumption, ophthalmoscopy, clinical pathology, gross pathology, organ weights or histopathology over 28 days [ 31 ]. Our findings for EMfCs were differenced from those observed upon investigation of the cell viability of 3T3-L1 adipocytes treated with 100 µg/mL of ethanol extract of mulberry leaves, because the samples were prepared using different methods and treated with different dosage.…”
Section: Discussionmentioning
confidence: 99%